2013
DOI: 10.1016/j.syapm.2013.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Mapping glycoconjugate-mediated interactions of marine Bacteroidetes with diatoms

Abstract: The degradation of diatoms is mainly catalyzed by Bacteroidetes and this process is of global relevance for the carbon cycle. In this study, a combination of catalyzed reporter deposition-fluorescence in situ hybridization (CARD-FISH) and fluorescent lectin binding analysis (FLBA) was used to identify and map glycoconjugates involved in the specific interactions of Bacteroidetes and diatoms, as well as detritus, at the coastal marine site Helgoland Roads (German Bight, North Sea). The study probed both the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 67 publications
6
43
0
Order By: Relevance
“…For staining procedures involving multiple staining and washing steps, agarose‐embedding of sections added structural stability and improved section integrity and preservation. However, agarose‐embedding is limited by non‐specific binding to agarose by lectins (as observed in our study and reported by Bennke et al ). Staining prior to embedding in cryogel may be considered to sidestep this problem, but limits the possibility of combining incompatible stains across consecutive slices and excludes aggregates embedded in situ.…”
Section: Assessmentsupporting
confidence: 81%
“…For staining procedures involving multiple staining and washing steps, agarose‐embedding of sections added structural stability and improved section integrity and preservation. However, agarose‐embedding is limited by non‐specific binding to agarose by lectins (as observed in our study and reported by Bennke et al ). Staining prior to embedding in cryogel may be considered to sidestep this problem, but limits the possibility of combining incompatible stains across consecutive slices and excludes aggregates embedded in situ.…”
Section: Assessmentsupporting
confidence: 81%
“…Association of Polaribacter spp. with phytoplankton was also observed in the open North Atlantic (Gó mez-Pereira et al, 2012) and the coastal North Sea (Bennke et al, 2013) and has been inferred in a recent study on an Antarctic polynya (Kim et al, 2013). Because of their presence in cold and temperate waters, in oligotrophic and copiotrophic nutrient regimes within open ocean and coastal zones, members of the genus Polaribacter have recently been recognized as 'widely distributed in marine habitats' (Nedashkovskaya et al, 2013).…”
Section: Introductionmentioning
confidence: 78%
“…These findings imply a possible relevance of this bimodal interaction in algal bloom initiation and termination (Riclea et al., ; Wang et al., ), especially once the dominance of the same phylotypes is assessed in the bacterial communities associated with both bloom phases. In addition, quality and amount of the algal‐released compounds, that depend on algal species and its physiological status, would define phylogenetic structure (Bennke, Neu, Fuchs, & Amann, ; Christie‐Oleza, Scanlan, & Armengaud, ; Xing et al., ) and successional pattern of the associated bacterial community (e.g., Bagatini et al., ; Grossart et al., ; Teeling et al., ).…”
Section: Introductionmentioning
confidence: 99%